Valorisation of fruit and vegetable discards by fungal submerged and solid-state fermentation for alternative feed ingredients production. (1st March 2021) - Ibarruri, Jone; Cebrián, Marta; Hernández, Igor
Abstract: The present research describes an integral strategy for valorisation of fruit and vegetable discards (FVd) in feeding application, using solid-state fermentation (SSF) and submerged fermentation (SmF), for both solid and liquid fractions obtained during these by-products handle and processing, using a strain of Rhizopus sp. After SSF, fermented biomass had 1.9 times higher protein content (up to 20.2 ± 1.7% DM) than the original mass and an improved amino acid (AA) profile (45.7 ± 1.8% essential AAs). Fatty acid (FA) profile was also modified during fermentation process, with higher monounsaturated (MUFA) and lower polyunsaturated fatty acid (PUFA) percentage in the final product compared with initial substrate. Phenolic compound concentration was double in final biomass than in initial substrate (up to 8.9 ± 1.5 mg GAE/g DM) and fermented product had higher antioxidant activity (DPPH reduction of 81.3 ± 7.7% and TEAC of 3.6 ± 0.3 mg/g DM). Compared with previously reported results, fruit complementation with vegetables increased the available nitrogen and resulted in higher biomass production. The fruit and vegetable leachate (FVL) obtained by centrifugation was treated by SmF and led, per liter of substrate, to 10.6 ± 1.4 g of fungal biomass and 3.3 g protein after 7 days of fermentation. Obtained fungal biomass was rich in PUFAs (27.1 ± 7.2% of total FA) and had an AA profile comparable to soybean meal, with 45.3 ± 1.5% of essential amino acids (E AA) . In conclusion, results demonstrate that combined solid and liquid fermentation is a successful strategy for FVd valorisation to produce valuable alternative feed ingredient due to their high protein and the well-balanced lipid content and amino acid profile. Graphical abstract: Image 1 Highlights: SSF enriches fruit and vegetable discards in protein and amino acid profile, highly improving their suitability as animal feed. Rhizopus fermentation of fruit and vegetable leachate leads to a 31% protein biomass, with being a valuable alternative protein. A combined solid and liquid Rhizopus fermentation is a successful strategy for a complete fruit and vegetable valorisation. Solid and liquid fermentation lead to valuable and sustainable alternative protein sources for animal feed formulations.